Development and evaluation of taxon-specific primers for the selected Caudovirales taxa - Newase, Sandeep K.; Gupta, Alka; Dastager, Syed G.; Kapadnis, Balu P.; Shashidhar, Ravindranath (Virus Research, 2019)
The phage taxonomy is primarily based on the morphology derived from Transmission Electron Microscopic (TEM) studies. TEM based characterization is authentic and accepted by scientific community. However, TEM based identification is expensive and time consuming. After the phage isolation, before analysis TEM, a DNA based rapid method could be introduced. The DNA based method could dramatically reduce the number of samples analyzed by TEM and thereby increase the speed and reduce the cost of identification. In the present work, four environmental phage isolates were identified based on TEM studies and genome size. The identification of these four phages was validated using DNA based method. The taxon-specific DNA markers were identified through multiple sequence alignments. The primers were designed at conserved genes (DNA polymerase or integrase) of 4 different phage taxa viz. family Ackermannviridae, genus Jerseyvirus, genus T4virus, and genus P22virus. These primers were evaluated using both in vitro and in silico approach for the amplification of the target taxons. Majority of the primer sets were found to amplify member species of the targeted taxa in vitro. In In silico analysis, six primer sets intended for identification of family Ackermannviridae showed positive amplification of >= 86.7% classified species. Further, the primers targeting the genus Jerseyvirus and T4virus showed the amplification of 53.8% and >= 84.6% species, respectively. The present work is a case study performed to explore the possibility of use of taxon-specific primers for identification and taxonomic studies of newly isolated phages to supplement the TEM.
Keywords: Bacteriophage; DNA markers; Pcr; Primers; Taxonomy; TEM